THE ANALYSIS OF TENSE CHOICE IN NATIONAL COLUMN IN THE JAKARTA POST NEWSPAPER - Nur Habibah; Levandra Balti (Universitas Muhammadiyah Muara Bungo, 2021)
The purpose of this research is to know what are the tense used in Jakarta Post newspaper in National column and to know what is the most and the less tense that used in the Jakarta Post newspaper in National column. Tense is a unit consisting of verbs that explain and emphasize information, which amounts to 16 tenses, the four main points of these tenses are past tense, present tense, future tense, and past future, then accompanied by four kinds of activities including simple, continuous, perfect and perfect continuous. The source data of this research is Jakarta Post newspaper in the national column and the secondary data are books, journal that supporting the main data in doing the research. This research is qualitative descriptive research that used library research. The result of this research is there are 9 tenses that used in National column in the Jakarta post newspaper they are 47 of simple present, 4 of present continuous, 31 of present perfect, 132 of simple past, 1 of past continuous, 2 of past perfect continuous, 7 of simple future, 12 of past future and 13 of past perfect. The most tense that used in National column in the Jakarta Post newspaper is simple past and the less tense that use in the Jakarta Post newspaper is past continuous.